Juhud Muhammad Ali Pasha fi al-Nahdah al-Lughah al-'Arabiyah wa Adabiha fi al-Diyar al-Misriyah - Ahmad Baihaqi Anas; Syahrial Syahrial (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
This study aims to explore the efforts and endeavours of Muhammad Ali Pasha in the revival of the Arabic language and literature in the country of Egypt. This qualitative desk-based research relied on an inductive and analytical approach to trace the places of this importance and then analyze them. The research concluded that the efforts and attempts of Muhammad Ali Pasha to promote the Arabic language and literature when he was the ruler of Egypt, such as sending Egyptian scholars to Europe on scientific missions, contributed to the emergence of Arabic language and literature scholars in Egypt.